Radical treatment for blastomycosis following unsuccessful liposomal amphotericin. Issue 12 (December 2022) - Chew, Christopher; Thapa, Nikhilesh; Ogbuagu, Henry; Varghese, Merin; Patel, Dhaval; Abbas, Raza; Oh, Jason; Teshome, Molla; Mohammed, Khaja; Saleem, Sohail; Aggarwal, Deepak; Barns, Barry; et al.
Summary: Pulmonary blastomycosis is a respiratory disease that is caused by the fungus Blastomyce s spp, which is acquired through inhalation of the fungal spores. Blastomycosis is relatively uncommon, with yearly incidence rate of 1–2 cases per 100 000 people. Blastomycosis is a disease that is endemic to the midwest and southern regions of the USA, most commonly affecting immunocompromised patients. About 50% of patients are asymptomatic, but for those who progress to acute respiratory distress syndrome (ARDS) mortality can be as high as 80%. Patients with severe blastomycosis are initially treated with intravenous amphotericin B, followed by long-term itraconazole maintenance therapy. In this Grand Round, we present the case of an immunocompetent 35-year-old man diagnosed with chronic pulmonary blastomycosis who had a poor response to 10 days of intravenous liposomal amphotericin B (L-AmB). He was endotracheally intubated and eventually cannulated for extracorporeal membrane oxygenation (ECMO), due to worsening respiratory function. L-AmB was replaced with a continuous infusion of intravenous amphotericin B deoxycholate (AmB-d). He improved significantly and was decannulated from ECMO on day 9 of AmBd continuous infusion and extubated on day 12 Although L-AmB is considered first-line treatment for blastomycosis, mortality remains high for patients with ARDS associated with blastomycosis. This case highlights the importance of considering AmB-d continuous infusions for patients with severe blastomycosis who might have poor clinical responses to L-AmB.